Follicular Occlusion Syndrome — a Possible Option of Follicular-Retension Origin of Pilonidal Sinus - D. D. Shlyk; M. N. Pikuza; Yu. E. Kitsenko; A. S. Pirogova; N. B. Paramonova; R. T. Rzaev; N. P. Teplyuk; P. V. Tsarkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to analyze and evaluate the clinical and morphological manifestations of pilonidal sinus disease (PSD) as a part of follicular occlusion syndrome (FOS).Materials and methods. In the Clinic of Coloproctology and Minimally Invasive Surgery, 80 patients with PSD underwent surgeries from November 2018 to December 2019: 62 (77.5 %) patients — with primary PSD, 18 (22.5 %) — with recurrence of the disease.Results. There were 80 patients, 6 patients (9.7 %) with primary and one (5.6 %) patient with recurrent cyst had concomitant manifestations of follicular occlusion syndrome. Thus, the frequency of combination of PSD with other variants of FOS course amounted to 8.8 %. Hidradenitis suppurativa of axillary and inguinal areas was found in 5 out of 7 patients. Acne conglobata, as one of the components of FOS, was noted in three patients. Dissecting cellulitis of the scalp was diagnosed in one patient. Follicular occlusion triad was observed in two patients. Follicular occlusion tetrad was not noted in any observation. All patients were treated with excision of the pilonidal sinus disease with local tissue-plasty of the defect. At present, no recurrences have been noted in any of the cases, and the mean follow-up time was 14 ± 5.6 months (6–27 months). PSD as a manifestation of follicular occlusion syndrome is characterized by a more cranial and more superficial location of the cavity in the sacrococcygeal region. According to the data of histologic examination of patients with FOS, the morphologic picture is identical with patients with isolated PSD. All patients with confirmed FOS have received pathogenetic local and conservative therapy. After the therapy remission of combined diseases is noted.Conclusion. Deroofing of the lining of the cavity, often used in dermatologic practice, along with complex treatment within the framework of multidisciplinary (together with a dermatologist) management of patients with FOS, looks promising.